Paleoecological reconstruction of a modern whitebark pine (Pinus albicaulis) population in Grand Teton National Park, WY - Kelly, Kyleen E. (Kansas State University, 2014)
Whitebark pine (Pinus albicaulis) is a critically threatened North American conifer. In modern times, it has experienced a significant decline in population due to pine beetle infestations, blister rust infections, fire suppression, and climate change. While climate, fire, and vegetation are strongly linked on regional and global scales, the relative roles of these three factors are not well-documented during the Holocene in high elevation mountain sites of North America. Recent anthropogenic changes in climate and fire management practices are underway, but the potential responses of subalpine vegetation to these environmental changes remain relatively unknown. Here, I documented the paleoecology of a watershed surrounding an unnamed, high-altitude pond containing a large number of whitebark pine trees located at 2805m elevation in Grand Teton National Park, U.S.A. Using a 1.5 meter lacustrine sediment core collected in 2010, I generated a Holocene-scale fire and vegetation record using fossil pollen, charcoal, and macrofossils preserved within the core. I also conducted a dendrochronological study of the current stand of whitebark pine in the watershed to determine both approximate dates of establishment and responses to past climate change of this modern stand. Sedimentary charcoal data indicate significant variability in both fire frequency and fire intensity during the Holocene. The fire regime observed in the past 1000 years is seemingly unprecedented at this site, with lower fire frequency and higher fire intensity than any other time during the Holocene. Sedimentary pollen data suggest the study site has been primarily dominated by whitebark pine until the last 1000 years, with brief periods of vegetation dominated by non-arboreal taxa that indicate the presence of either successional dynamics or shifts in treeline location. Ages of individual living whitebark pine trees average 365 years, and dendrochronology data suggest that ring widths of the current stand have been declining since 1991. Statistical analyses of PRISM climate data with ring width data suggest that this decrease in annual growth is likely the result of decreased growing season temperature ranges driven by a warming climate. While this stand of whitebark pine is threatened by both warming climate and fire suppression, there is the potential for low-intensity prescribed burns to play a role in conservation and restoration management plans for this threatened conifer.
Keywords: paleoecology; Whitebark pine; fire history; climate; Geography (0366)